The concept of Arduino based on Wireless communications for flood warning system - Md Kamal, Mahanijah; Muhammad Sabri, Aqil (International Journal of Engineering and Technology, 2018)
Wireless communication for flood monitoring is developed to observe the status of flooding which could alert people who were in the area when it happens. Flood is a very common problem that Malaysian faced every year caused by the change of climate and also due to urbanization. These floods can cause a lot of damages and can even endanger to human lives. The flooding can be caused by the overflowing of rivers or drains in the affected area. Problems in rural areas near the river bank, not all equipped with flood warning system. Flood warning system is usually found in the main streets with limited warning distance. Therefore, it is necessary to put a wireless communication system that can detect the rising water levels during flooding and also gives warn the local residents especially those who live along the river banks. This system can be used as flood monitoring tool as well as for evacuation during save and rescue operation. The purpose of this paper is to propose a wireless communication based on Arduino system that can help the local residents by detecting the water levels and give an early warning when a flood occurs. Basically, there are two part of the system which are the sensor node and the base station that can generate warning signal during flooding to the affected area.Â